Comparison between Various Approaches for Customer Relationship Management in Data Mining (International Journal of Engineering and Computer Science, 2017)
In this paper various techniques used for CRM in data mining are defined and compared with each other. Data mining is a useful and powerful tool for any organization especially for marketing people. Data mining is used in managing relationships with customers. Data mining process can be extremely useful for Medical practitioners for extracting hidden medical knowledge. It would otherwise be impossible for traditional pattern matching and mapping strategies to be so effective and precise in prognosis or diagnosis without data mining techniques